Pengaruh Dari Good Corporate Governance Terhadap Nilai Perusahaan Dengan Menggunakan Meta Analisis - Cynthia Agatha; Canita Liani; Nathalie Nathalie; Carmel Meiden (Universitas Malahayati, 2023)
The purpose of this research is to integrate the influence of Good Corporate Governance (GCG) on firm value. Basically, the spirit and spirit of Good Corporate Governance (GCG) is viewed using the perspective of agency theory, intended so that management actions are in harmony with the goals and expectations of creditors and shareholders. This study uses a literature study with a meta-analysis extension that integrates a number of 20 published articles obtained using the PoP (Publish Or Perish) application. The limitation of the search for articles is based on the years 2012-2022, and applies inclusion inclusion criteria and the application of the keywords Good Corporate Governance and corporate value. The result of the integration is the implementation of Good Corporate Governance (GCG) which will assist the company in achieving high value, so that it will provide added value for shareholders in a sustainable manner in the long term.